Children's unmet palliative care needs: a scoping review of parents' perspectives. Issue 4 (19th July 2019) - Constantinou, Georgina; Garcia, Rebecca; Cook, Erica; Randhawa, Gurch
Abstract : Background: Children with life-limiting conditions often have complex needs, making it challenging for services to provide satisfactory care. Few studies consider whether services actually meet families' needs by exploring and identifying the parents' perspectives of unmet needs. Aim: To identify what published evidence is available on the unmet needs of children with life-limiting conditions and their families, from the perspective of parents, internationally. Eligibility criteria: Inclusion criteria : papers from the perspective of parents of children aged 0–19 years, who have a life-limiting condition and are receiving palliative care. Exclusion criteria : those papers not written in English, not reporting primary research and discussing children who died from stillbirth, accidental or unexpected circumstance. Charting methods: A scoping review was conducted in accordance with the methods of Arksey and O'Malley. Sources of evidence: The electronic databases PubMed, MEDLINE, CINAHL and PsycINFO were searched. Key terms included: parent, needs, met/unmet/satisfaction, palliative/supportive/end of life care, life-limiting/life-threatening illness, infants/children/young people. Results: Total hit indicated 5975 papers for screening. Fifty-five papers met the scoping review criteria. The majority used mixed-methods approaches inclusive of: questionnaires, self-report measures, in-depth interviews, focus groups, case record analysis and art-based workshops. Unmet needs included: respite care, coordination and organisation of care, psychological support and professional communication skills. Conclusions: The findings suggest many unmet needs from the parent's perspective, across several aspects of the Quality Standards and Children's Palliative Care Frameworks. Further research is needed which explores the parent's unmet needs in palliative care services.